Optimization of Succinic Acid Production by Actinobacillus sp. NP9-aA7 using Plackett-Burman Design Coupled with Box-Behnken Design - Sukanya Phuengjayaem (Science Faculty of Chiang Mai University, 2019)
The potential succinic acid bacterium, isolate NP9-aA7, was isolated from bovine rumen fluid. The phenotypic characterization and phylogenetic analysis based on the 16S rRNA gene sequence indicated that the isolate NP9-aA7 was identified to Actinobacillus succinogenes. The statistical methods combining Plackett-Burman Design (PBD) and Box-Behnken Design (BBD) were developed to optimize the process. The key factors consist of glucose 74 g/L, yeast extract 30 g/L, and MgCO3 60 g/L which gave a maximum succinic acid to 60.09 g/L with a yield of 0.8161 g/g glucose after 36 h. Batch fermentations in a 2-L fermenter leading to the highest succinic acid production which validated the model with the succinic acid of 58.08 g/L after 27 h. Moreover, the CO2 of 50.66 kPa and alkaline neutralizers (45 g/L of MgCO3 and 15 g/L of Mg(OH)2) enhanced succinic acid to 72.93 g/L with a yield of 1.393 g/g glucose after 24 h. When using SSH 40 g/L as a carbon source, the succinic acid of 27.70 g/L was obtained after 48 h. A. succinogenes NP9-aA7 has a potential for succinic acid production and combined statistical methods were powerful for optimizing the process.